Una micosis en roedores del género Mus en la campiña de Arequipa - Escomel, E. (1919)
He has a few days, my indefatigable teacher Mr. Dr J. HUNTER, sent me to study the mouse depicted in Figure 1 by the intense fungal attack that we describe. It is noteworthy that a year ago we sent a field rat (Mus ratus), attack of the same disease, as from the mouse, which motivates this paper, Tingo the countryside around Arequipa. The mouse (Mus musculus), which still came alive in our hands, had been caught in an alfalfa. As soon as the animal felt persecuted, ran with power and violence, but with some puzzlement, until he could be there. I draw attention to this fact, because the fungus had become totally blind to the animal. Fungal infection is not intoxicating either, as having plenty of food at their disposal, rodent health was good and identical to that of their healthy like, in the same country region complexion.